A cross-sectional study of factors associated with regular dog walking and intention to walk the dog - Carri Westgarth; Robert M. Christley; Hayley E. Christian (BMC, 2022)
Abstract Background Dog walking is important for public health and dog welfare, yet some owners do not walk with their dogs regularly. This study examined factors associated with participation in regular dog walking and intention to dog walk, in order to inform physical activity interventions. Methods 191 dog-owning adults from a UK community were surveyed about their participation in dog walking, intention to dog walk, attitudes and behavioural beliefs regarding dog walking, and dog and owner demographics. Principal components analysis identified owner profiles regarding attitudes and behavioural beliefs about dog walking. Univariable and multivariable logistic regression were used to identify factors associated with being a regular dog walker (achieving 150mins per week of dog walking) and having a high intention to dog walk (at least 30 mins per day for at least 5 days per week over the next month). Results Participants walked with their dogs for a median 7 times/week and 230 total minutes/week; regular dog walkers 9 times/week (400 minutes/week), compared to twice/week for irregular dog walkers (45 minutes/week). Being a regular dog walker was positively associated with having a high level of intention to walk the dog in the next month (OR=12.1 95%CI=3.5-42.4, P<0.001), being married or living with a partner (OR=33.5, 95%CI=2.5-458.8, P=0.01), and higher scores on a dog walking habit index (OR=2.1, 95%CI=1.3-3.5, P<0.01). However, higher support from friends for walking was negatively associated with being a regular dog walker (OR=0.3, 95%CI=0.1-0.7, P<0.01). High intention to dog walk was associated with female owners (OR=4.7, 95%CI=1.2-18.5, P=0.03), dogs that lay on the sofa (OR=6.9, 95%CI=1.5-31.8, P=0.01), high levels of self-efficacy to walk the dog over the next month (OR=5.8, 95%CI=1.5-21.9, P=0.01), owner type with an attitude of high responsibility and enjoyment from walking (OR=2.1, 95%CI=1.2-3.8, P=0.02), and higher scores on a dog walking habit index (OR=1.9, 95%CI=1.0-3.7, P=0.05). Reporting someone else walks the dog was negatively associated with high intention (OR=0.1, 95%CI=0.0-0.7, P=0.02). Conclusions Interventions to promote dog walking may benefit from increasing intention to dog walk in male owners, forming schedules and routines that involve multiple household members in dog walking, and establishing habits around dog walking. Interventions may also need to address how to overcome barriers and perceived challenges in regards to self-efficacy of dog walking, that may prevent intention from being translated into action.